Clock genes in pancreatic disease progression: from circadian regulation to dysfunction - Tiankuo Zheng; Kunpeng Wang; Qiao Shi; Lilong Zhang; Qihao Yan; Wanrong Jiang; Chen Chen; Kailiang Zhao; Jiarui Feng; Weixing Wang (Annals of Medicine)
Background Circadian rhythms, governed by core clock genes, are essential for maintaining metabolic, endocrine, and immune homeostasis. Disruption of these rhythms has been increasingly implicated in the pathogenesis of various pancreatic diseases.Objective This review summarizes current evidence on the role of circadian rhythm disruption in pancreatic diseases, including type 2 diabetes (T2D), type 1 diabetes (T1D), pancreatitis, and pancreatic cancer (PC), with a focus on underlying mechanisms involving clock gene dysregulation.Recent findings In T2D, dampened oscillations of clock gene expression in pancreatic islets are associated with impaired insulin secretion and loss of cellular synchrony. In T1D, circadian dysregulation enhances immune activation and reduces β-cell tolerance, accelerating disease progression. In pancreatitis, especially in chronic forms, loss of core clock components such as Bmal1 exacerbates pancreatic stellate cell activation, fibrosis, and inflammatory cytokine release. Additionally, circadian disruption has been linked to pancreatic tumorigenesis, suggesting a potential role of clock genes in early cancer development through modulation of the inflammatory microenvironment and stromal remodeling.Conclusion Circadian clock genes play a multifaceted role in pancreatic disease pathophysiology, extending beyond metabolic regulation to influence immune responses, inflammation, and tumorigenesis. Understanding these mechanisms may inform the development of novel circadian-based therapeutic strategies for pancreatic disorders.